THE IMPORTANCE OF THE SERRA GERAL AQUIFER SISTEM TO THE SOYBEAN CULTURE - Ernani Francisco Rosa Filho; Eduardo Chemas Hindi; Luiz Eduardo Mantovani; André Virmond Lima Bittencourt (Revista Águas Subterrâneas, 2006)
The lack or insufficient amount of rain fall during the blooming and growing periods of soybeans are one of the major factors that cause either complete loss or large reductions of harvest areas in the southern region of Brazil. Within the Paraná State the soybeans agriculture covers an area of approximately 3,650,000 hectares (36,500 km2), which is equivalent to nearly 18.3% of the State’s total geographical surface. Hence, these areas need a minimum of 30 mm per month of rain fall in order to maintain the sustainable activity in the long term, taking for instance the extensive loss of soybeans crop that took place in February 2005 due to the lack of rain. In order to flourish, soybeans needs 1 L.day-1.m-2. The yield of wells drilled into the Serra Geral Aquifer System (SASG) can vary from 21 a 35 m3.h-1, with the exception of the ones drillled inside the Iguaçu river basin, that show average yield of 5 m3.h-1. In almost 90% of the wells, water can be found within less than 170 m deep. In wells which discharges vary from 25 m3.h-1 to 100 m3.h-1, their capacity to irrigate an soybean crop, can cover an area of 600,000 m2 and 2,400,000 m2, respectively. SASG waters presenta low to medium sodium risk and also a predominately low risk of salinity.